THE INFLUENCE OF VIRAL MARKETING, BRAND IMAGE, FOOD QUALITY AND FOOD PRICE MIXUE ON REPEAT ORDERS FOR GEN Z CONSUMERS IN MEDAN CITY - Sherly Sherly; Violyn Qian; Fajar Rezeki Ananda Lubis; Thezar Fiqih Hidayat Hasibuan (Transpublika Publisher, 2024)
The objective of this study is to investigate how Viral Marketing, Brand Image, Food Quality, and Food Price affect Repeat Orders at Mixue Medan. This study falls under the category of quantitative research. The research will involve all customers who have bought items at Mixue in Medan City in 2022, a population too vast to quantify. With 18 question items in the research, a minimum of 90 samples will be needed. The findings from the study indicate that the initial hypothesis has been confirmed, namely Viral Marketing influences Repeat Orders at Mixue Medan, the second hypothesis is accepted, namely Brand Image influences Repeat Orders at Mixue Medan, the third hypothesis is accepted, namely Food Quality influences Repeat Orders at Mixue Medan, the fourth hypothesis is accepted, namely Food Price influences Repeat Orders in Mixue Medan and the fifth hypothesis is that Viral Marketing, Brand Image, Food Quality and Food Price influence Repeat Orders in Mixue Medan.